2021
DOI: 10.1177/0894439321998357
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Empirical Links Between Digital Social Pressure, Personality, Psychological Distress, Social Support, Users’ Residential Living Conditions, and Smartphone Addiction

Abstract: Based on the recent scientific literature on the social ecology of smartphone addiction, we have examined the empirical relationship between social digital pressure (SDP) and smartphone addiction by also looking at the influence of users’ personalities, psychological distress, social support, and residential social living conditions on this addiction. The analyses were carried out on a nationally representative sample of 2,820 Spanish smartphone users. The results of the causal and multigroup models (structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…However, staff participants cited the fear of losing online friends as a leading cause of overusing smartphones among students. These findings correspond with the findings of previous studies which concluded that social pressure [ 72 , 73 , 74 ] and fear of losing a connection [ 75 , 76 ] were triggers for smartphone addiction. For instance, a study conducted among 2820 Spanish smartphone users found that higher levels of social pressure were associated with higher levels of smartphone addiction [ 73 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, staff participants cited the fear of losing online friends as a leading cause of overusing smartphones among students. These findings correspond with the findings of previous studies which concluded that social pressure [ 72 , 73 , 74 ] and fear of losing a connection [ 75 , 76 ] were triggers for smartphone addiction. For instance, a study conducted among 2820 Spanish smartphone users found that higher levels of social pressure were associated with higher levels of smartphone addiction [ 73 ].…”
Section: Discussionsupporting
confidence: 91%
“…A meta-analysis reported that smartphone addiction was associated with greater social distress levels among medical students [ 14 ]. However, another study suggested that persons experiencing psychological distress use their smartphone more often to decamp from negative feelings due to distress, indicating that distress may be an antecedent of smartphone addiction [ 13 ]. The current study and literature echo the association between smartphone addiction and psychological distress, which may lead to several negative implications that include, but are not limited to, attrition from study or work, impaired performance, problematic health behaviors, anxiety, panic disorder, and depression [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…One seemingly harmless element that could be related to an increased risk of cyberfraud victimization would be the need for users to expand their communication capabilities with other users through the use of increasingly sophisticated applications. These communication applications are designed to retain and capture users' attention (Kushlev et al, 2019), so social digital pressure could be an undesirable outcome (Gui & Büchi, 2021;Herrero, Torres, Vivas, Arenas, et al, 2021) associated with the design of these applications. Recent empirical evidence suggests that social digital pressure may become an important antecedent of smartphone addiction (Herrero, Torres, Vivas, Arenas, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These communication applications are designed to retain and capture users' attention (Kushlev et al, 2019), so social digital pressure could be an undesirable outcome (Gui & Büchi, 2021;Herrero, Torres, Vivas, Arenas, et al, 2021) associated with the design of these applications. Recent empirical evidence suggests that social digital pressure may become an important antecedent of smartphone addiction (Herrero, Torres, Vivas, Arenas, et al, 2021). Thus, personal tendencies to seek fun or connectivity with other users could lead to a higher risk of cyberfraud victimization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation